Modernity, Covid-19 and coloniality in Peru. Introductory notes - Mejía Navarrete, Julio (2020)
The coronavirus pandemic expresses the general trends of the modern global pattern, whose serious threats outline a gray horizon of coloniality. The study describes some central ideas in the peruvian social life, the important thing is to highlight some elements that allow to understand current moments. It is interesting to distinguish for its analysis the transformations of the modern global pattern and the possible impacts they generate in the country.